Educational needs of the esports industry: A Delphi study - Leis, O.; Sharpe, B. T.; Moriconi, M.; Ascenso, I.; Barkoukis, V. (Journal of Electronic Gaming and Esports, 2025)
Although esports has grown significantly over the past decades with educational programs expanding globally, there is a lack of understanding of the specific areas where students in esports require development, including technical and interpersonal skills essential for success in emerging disciplines. To identify these educational needs in esports and thereby inform future research and educational programs, a Delphi study including global experts was conducted. Using an online survey, 25 experts prioritized educational needs for esports based on existing programs and suggest missing elements. Following this survey, 20 experts joined panel discussions to discuss the survey ranking and reach consensus. The study highlighted “Entrepreneurship and Innovation,” “Sport Science and Health,” and “Esports Management and Business” as the top three educational needs. Although aspects such as “Technology and IT Skills,” “Broadcasting and Journalism,” and “Game Design and Development” were ranked lower, the panels stressed the role of every educational need identified within this study and the constant-changing environment, including short- and long-term needs. The findings underline the necessity for evidence-based educational programs to support the esports industry and facilitate the transition from education to employment. Further research is needed to adjust educational pathways to keep up with the evolving esports industry.